Pharmaceutical Staff Behavior and Patient Satisfaction in Drug Information Services: A Cross-Sectional Study in Pekanbaru, Indonesia - Fina Aryani; Sari Putri Ramadhani; Husnawati Husnawati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2026)
The provision of drug information by pharmaceutical staff in pharmaceutical services aims to prevent medication errors and affect patient satisfaction. Satisfaction results from a patient's assessment of health services by comparing the services received with what the patient expects. This study aims to investigate the effect of pharmaceutical staff behavior on patient satisfaction with drug information at pharmacies in Pekanbaru City. This study employs a descriptive-analytic observational/survey design with a cross-sectional approach. Data collection techniques were carried out simultaneously. The samples in this study consisted of 32 pharmaceutical staff members and 105 patients from 15 pharmacy branches. Sampling for pharmaceutical staff was conducted using the saturated sample method, while patient samples were collected using purposive sampling. A satisfaction questionnaire was prepared based on the satisfaction dimensions. Positive behavior was observed in 62% of cases, while harmful behavior was observed in 38%. The average percentage of the gap between expectations and services is 0.70. This indicates that the services provided to patients at the pharmacy exceed their perceived expectations. The Chi-Square test results yielded a p-value of 0.000, indicating a significant influence between the behavior of pharmaceutical staff and patient satisfaction in providing drug information at pharmacies in Pekanbaru City.